Duchowieństwo dekanatu Skała w świetle wizytacji z 1618 roku - Markiewicz, Tomasz (Archiwa, Biblioteki i Muzea Kościelne, 2010)
The records of the Cracow Archdeanery from 1617 to 1619 contain a wealth of material, which enables the learning of the work, life and habits of the clergy. This applies specifically to the internal inspections, which enables understanding the clergy not just in regard to numbers or structure, but also by means, so for unknown, allows the group to be viewed in the light of ministry and morality. The Skała Deanery compared to other deaneries, lying more to the east, was characterized by the lowest numbers of ministers per statistical parish. In practice, the ministry in the majority of the parishes in the deanery was carried out by only one priest. The information, relating to the ministry and habits of the clergy, received from the inspector and witnesses under oath has allowed the precise determination of the extent of the observed phenomena. The inspection does not indicate any scandalous failings in the religious education of the faithful. A serious obstacle to effective ministry was the fact that nearly 30 % of parish priests did not reside in the parishes under their care. This problem dating from the period of the Middle Ages as well as during the time of the implementation of the Tridentine Reforms had remained, as yet, unsolved. The clergy’s morality left much to be desired, they were universally accused of drunkenness and the keeping of non-permitted contacts with women. In the case of the former, as we have shown, the accusations were quite diverse. According to very careful estimates, the behavior, with respect to alcohol, of 15 % of the clergy was scandalous. Transgressions of a sexual nature were no less widespread, which according to the testimony of witnesses affected 41 % of ministers. A significant majority of the accused (71 %) cohabitated with women, while the acts of the rest were more of a short-term character, often quite shocking. It is worth remembering, that the veracity of the testimony of witnesses is borne out by their agreement with each other and the fact that they were made under oath. The emerging picture leads to the conclusion that ministers of the Skała Deanery, raised in the atmosphere of the implementation of the Tridentine Reforms, were far removed from the ideal of ministers carrying out their functions as administrators and as leaders of parishioners, who consciously and purposefully guided the spiritual lives of their parishes.